Organ Dysfunctions among Deaths in Critically Ill Patients - Maharjan, Leison; Shah, Aarzoo; Bajracharya, Uday; Shrestha, Gambhir (Journal of Nepal Health Research Council, 2018)
Background: Multiple organ failure is recognized as the final pathway preceding majority of deaths in intensive care unit. This study aims to find out the prevalence of organ dysfunctions/ failures in patients at the time of their demise irrespective of the underlying diseases in a tertiary care hospital. Methods: This study was done in medical intensive care unit of Blue Cross Hospital. Medical records of all deceased patients in two years period were thoroughly reviewed retrospectively. Status of six organ systems was categorized into five sub-groups: No organ dysfunction, Mild organ dysfunction, Acute organ failure, Acute-on-chronic organ failure, and Chronic organ failure. The proportion of organ dysfunction involved was analyzed along with other variables.Results: Among 204 deaths, majority 165 (80.9%) had Multiple Organ Dysfunction Syndrome. Circulatory system was most affected system with “acute organ failure” 134 (65.5%) followed by acute respiratory failure 128 (62.7%), and acute neurologic failure 114 (55.8%). Neurologic system was most affected with “mild organ dysfunction” 47 (23%) followed by Respiratory system and Renal system. Of the patients who had chronic organ failures at the time of admission, 72 (81.8%) developed “acute-on-chronic failures”.Conclusions: Multiple Organ Dysfunction Syndrome was present in the majority of deaths in critically ill patients. Most common acutely failed organ was the circulatory system.